A Street of Seedsmen: Plant Retailers in Victoria Avenue, Whanganui - Jordan, Kate (Architectural History Aotearoa, 2024)
In the 1940s, seedsmen, florists and other plant retailers were generally located on main streets of towns and cities. This paper looks at Whanganui as a case study of the relationships between plant retailers and the landscape, people and capital. The challenges of researching businesses and quantitative history are woven throughout.